2015
DOI: 10.1007/s10342-015-0902-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil bulk density on sessile oak Quercus petraea Liebl. seedlings

Abstract: This article presents the results of laboratory examinations concerning the effects of soil bulk density on the growth of sessile oak Quercus petraea Liebl. seedlings. The soil for the study was collected from a nursery plot and then compacted into PCV pots in eight different bulk density levels ranging from 0.81 to 1.32 g cm -3 . Oak seedlings were cultivated in controlled conditions for 76 days after sowing. The growth and mass parameters of particular seedlings together with the parameters of the assimilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 47 publications
(58 reference statements)
8
26
2
Order By: Relevance
“…The biomass of Quercus robur was higher, but the high mortality of Quercus seedlings (according to the results of investigations) limits its application in phytoremediation. This is similar to the results of Kormanek et al (2015a), who reported that increased soil compaction had a negative impact on oak seedling growth. It is also worth noting that Kormanek et.…”
Section: How Can Trees Help Us In Waste Management?supporting
confidence: 93%
“…The biomass of Quercus robur was higher, but the high mortality of Quercus seedlings (according to the results of investigations) limits its application in phytoremediation. This is similar to the results of Kormanek et al (2015a), who reported that increased soil compaction had a negative impact on oak seedling growth. It is also worth noting that Kormanek et.…”
Section: How Can Trees Help Us In Waste Management?supporting
confidence: 93%
“…The repeated measurements of height revealed that high levels of soil compaction significantly reduced height growth since emergence. A reduction in above‐ground growth was reported for oak species ( Q. rubra, Q. coccinea, Q. alba , and Q. petraea ) in studies conducted under controlled environmental conditions (growth chamber or greenhouses) by Jordan et al (), Kormanek et al (), and Tworkoski et al () at the end of longer growing periods, that is, after 150, 76, and 40 days, respectively. Detrimental effects on the height of Q. robur seedlings grown in the field were also observed by Cambi, Hoshika, et al () in compacted soil after the first growing season.…”
Section: Discussionmentioning
confidence: 81%
“…), and reduced root length in plants (Kormanek et al . ). The high root length and surface area in the upper 0–10 cm would allow plants to capture the nutrients that are concentrated in that layer, which is particularly important in the tropics where leaching is high.…”
Section: Discussionmentioning
confidence: 97%
“…Soil organic matter and nutrient concentration decreased, while bulk density increased with soil depth in both forests (Addo-Danso SD, unpublished data). Indeed, increased soil bulk density may lead to roots with high SRA (Lõhmus et al 1989), reduced root surface area (Jamro et al 2015), and reduced root length in plants (Kormanek et al 2015). The high root length and surface area in the upper 0-10 cm would allow plants to capture the nutrients that are concentrated in that layer, which is particularly important in the tropics where leaching is high.…”
Section: Discussionmentioning
confidence: 99%